A Review of Translational Magnetic Resonance Imaging in Human and Rodent Experimental Models of Small Vessel Disease - Michael S. Stringer; Hedok Lee; Mikko T. Huuskonen; Bradley J. MacIntosh; Rosalind Brown; Axel Montagne; Sarah Atwi; Joel Ramirez; Maurits A. Jansen; Ian Marshall; Sandra E. Black; Berislav V. Zlokovic; et al. (Translational Stroke Research, 2021)
Cerebral small vessel disease (SVD) is a major health burden, yet the pathophysiology remains poorly understood with no effective treatment. Since much of SVD develops silently and insidiously, non-invasive neuroimaging such as MRI is fundamental to detecting and understanding SVD in humans. Several relevant SVD rodent models are established for which MRI can monitor in vivo changes over time prior to histological examination. Here, we critically review the MRI methods pertaining to salient rodent models and evaluate synergies with human SVD MRI methods. We found few relevant publications, but argue there is considerable scope for greater use of MRI in rodent models, and opportunities for harmonisation of the rodent-human methods to increase the translational potential of models to understand SVD in humans. We summarise current MR techniques used in SVD research, provide recommendations and examples and highlight practicalities for use of MRI SVD imaging protocols in pre-selected, relevant rodent models.

Homing, dispersal and mortality after translocation of long-lived land snails Placostylus ambagiosus and P. hongii (Gastropoda: Bothriembryontidae) in New Zealand - Ian Alexander Noel Stringer; Glen Richard Parrish; Gregory Howard Sherley (Molluscan Research, 2018)

Evaluating tree wētā (Orthoptera: Anostostomatidae: Hemideina species) as bioindicators for New Zealand national biodiversity monitoring - Corinne Watts; Ian Stringer; John Innes; Joanne M. Monks (Journal of Insect Conservation, 2017)

Population history and genetic bottlenecks in translocated Cook Strait giant weta, Deinacrida rugosa: recommendations for future conservation management - Daniel J. White; Corinne Watts; Julia Allwood; Diana Prada; Ian Stringer; Danny Thornburrow; Thomas R. Buckley (Conservation Genetics, 2017)

The biology of Placostylus ambagiosus (Pulmonata: Bulimulidae) in New Zealand: Part 1. Behaviour, habitat use, abundance, site fidelity, homing and the dimensions of eggs and snails - G. Richard Parrish; Ian A.N. Stringer; Greg H. Sherley (Molluscan Research, 2014)

The biology of Placostylus ambagiosus (Pulmonata: Bulimulidae) in New Zealand: Part 2. Population changes, growth, mortality and life expectancy - Ian A. N. Stringer; G. Richard Parrish; Greg H. Sherley; Darryl I. MacKenzie (Molluscan Research, 2014)

Saved from extinction? Establishment and dispersal of Mercury Islands tusked weta, Motuweta isolata, following translocation onto mammal-free islands - Ian Stringer; Corinne Watts; Danny Thornburrow; Rob Chappell; Robbie Price (Journal of Insect Conservation, 2014)

Towards implementation and achievement of sustainable biofuel development in Africa - Ian Duvenage; Ros Taplin; Lindsay C. Stringer (Environment, Development and Sustainability, 2012)

Are footprint tracking tunnels suitable for monitoring giant weta (Orthoptera: Anostostomatidae)? Abundance, distribution and movement in relation to tracking rates - Corinne Watts; Ian Stringer; Danny Thornburrow; Darryl MacKenzie (Journal of Insect Conservation, 2011)

Geographic parthenogenesis and the common tea-tree stick insect of New Zealand - MARY MORGAN-RICHARDS; STEVE A. TREWICK; IAN A. N. STRINGER (Molecular Ecology, 2010)

History of weta (Orthoptera: Anostostomatidae) translocation in New Zealand: lessons learned, islands as sanctuaries and the future - Corinne Watts; Ian Stringer; Greg Sherley; George Gibbs; Chris Green (Journal of Insect Conservation, 2008)

Possible rescue from extinction: transfer of a rare New Zealand tusked weta to islands in the Mercury group - Ian A. N. Stringer; Rob Chappell (Journal of Insect Conservation, 2008)